Rhetoric as a form of persuasion in disclosing poverty-related CSR activities in corporate disclosures: the case of Bangladesh - Hossain, Dewan Mahboob; Nik Ahmad, Nik Nazli; Siraj, Siti Alawiah (University of Malaya, 2017)
Research aim: This study aims to identify the persuasive strategies applied by Bangladeshi companies in disclosing poverty related corporate social responsibility (CSR) activities in their annual reports. Design/ Methodology/ Approach: This study applies the discourse analysis as an approach in exploring the narratives of Bangladeshi companies’ annual reports. It specifically focuses on the three classifications of Aristotle’s rhetoric while explanations are also drawn from the impression management theory. Research findings: This study concludes that the disclosures of the Bangladeshi companies’ CSR activities are rhetorical in nature. The analysis suggests that these companies try to portray themselves as pro-social and helpful towards the poor. Theoretical contribution/ Originality: Rather than focusing on ‘what’ was disclosed (which is the objective of most prior studies on CSR reporting in Bangladesh), this study highlights ‘how’ the disclosure was done. This study also focuses on a particular aspect which is poverty related and a linguistic analysis is used to perform the analysis which is unlike previous studies.